Theranostic tools against lung and breast cancers : through the lens of mature gold nanoparticles and emerging graphene - Baskaran, Savuntherii; Siew, Qi Yan; Tan, Michelle T.T.; Loh, Hwei-San (Oxford University Press, 2024)
In recent years, theranostic applications have emerged as promising tools in the fight against lung and breast cancers. This review aims to provide an in-depth exploration of the proof-of-concept theranostic applications of two cutting-edge nanomaterials: gold nanoparticles (AuNPs) and graphene. Nanotechnology plays a revolutionary role in cancer theranostics. AuNPs’ properties include high surface plasmon resonances, advantageous surface-to-volume ratio, remarkable photothermal conversion rates, and distinctive optical characteristics. Whereas graphene boasts high surface areas, optical transparency, and remarkable versatility in surface functionalisation. While AuNPs have long been recognised for their theranostic potential, this review spotlights the burgeoning role of graphene as a compelling choice for advancing theranostic applications in oncology with several exemplar studies. In fact, most recent advancements have witnessed the integration of AuNP-graphene nanocomposites in theranostic approaches targeting lung and breast cancers. Yet, there are still many intricate challenges that researchers face in harnessing the full potential of these nanomaterials in theranostics, from synthesis to clinical translation. This review provides valuable insights into both established and emerging nanomaterials. AuNPs show significant potential for diverse cancer theranostic applications, and graphene is rapidly evolving as a next-generation theranostic platform. The hybrid AuNP-graphene nanocomposite stands out as a promising candidate in the evolving landscape of cancer therapy, offering exciting prospects for future research and development.